1987
DOI: 10.1016/0014-5793(87)80292-2
|View full text |Cite
|
Sign up to set email alerts
|

A common bicyclic protein kinase cascade inactivates the regulatory enzymes of fatty acid and cholesterol biosynthesis

Abstract: A highly purified rat liver protein kinase phosphorylates and inactivates acetyl-CoA carboxylase, and causes rapid inactivation of microsomal HMG-CoA reductase in the presence of MgATP. Both effects are stimulated in an identical manner by AMP, and are greatly reduced by prior treatment of the kinase with purified protein phosphatase. The dephosphorylated kinase can be reactivated in the presence of MgATP, apparently due to a distinct kinase kinase, and this reactivation is stimulated by nanomolar concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
378
0
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 530 publications
(390 citation statements)
references
References 25 publications
11
378
0
1
Order By: Relevance
“…AMPK was first identified as an activity which, through the phosphorylation and inactivation of key biosynthetic enzymes [60], was responsible for rapidly shutting down fatty acid synthesis in the face of fuel depletion [58]. Subsequent cloning of the catalytic subunit of the enzyme [61] revealed that mammalian AMPK was a close homologue of the sucrose non-fermenting factor-1 complex in yeast and plants [62,63].…”
Section: Introductionmentioning
confidence: 99%
“…AMPK was first identified as an activity which, through the phosphorylation and inactivation of key biosynthetic enzymes [60], was responsible for rapidly shutting down fatty acid synthesis in the face of fuel depletion [58]. Subsequent cloning of the catalytic subunit of the enzyme [61] revealed that mammalian AMPK was a close homologue of the sucrose non-fermenting factor-1 complex in yeast and plants [62,63].…”
Section: Introductionmentioning
confidence: 99%
“…In cultured hepatoma cells, insulin rapidly leads to the activation of ACC. This activation is accompanied by inhibition of 5h-AMP-activated protein kinase [11], which is described as the major regulator of ACC [12][13][14]. In contrast, glucagon treatment of the cells produces further inactivation of the enzyme as the result of phosphorylation of ACC by the 5h-AMP-activated protein kinase [15].…”
Section: Introductionmentioning
confidence: 99%
“…LKB1/AMPK signaling induces several cellular processes, one of which is the control of energy metabolism through regulation of several downstream targets, including the metabolic enzymes acetyl-CoA carboxylase and HMG-CoA reductase (Figure 2) (Carling et al, 1987). By suppressing energy-consuming processes such as glycogen and lipid synthesis on the one hand, and enhancing energy-gaining pathways such as glycolysis on the other, AMPK activation aids in restoration of the cellular energy status (Kola et al, 2006).…”
mentioning
confidence: 99%